Early Hyperdynamic Sepsis Alters Coronary Blood Flow Regulation in Porcine Fecal Peritonitis - Boudart, Céline; Su, Fuhong; Pitisci, Lorenzo; Dhoine, Arnaud; Duranteau, Olivier; Jespers, Pascale; Herpain, Antoine; Vanderpool, Rebecca; Brimioulle, Serge; Creteur, Jacques; Naeije, Robert; Van Obbergh, Luc; et al. (Frontiers in Physiology, 2021)
Background: Sepsis is a common condition known to impair blood flow regulation and microcirculation, which can ultimately lead to organ dysfunction but such contribution of the coronary circulation remains to be clarified. We investigated coronary blood flow regulatory mechanisms – including autoregulation, metabolic regulation, and endothelial vasodilatory response – in an experimental porcine model of early hyperdynamic sepsis. Methods: Fourteen pigs were randomized to sham (n=7) or fecal peritonitis-induced sepsis (n=7) procedures. At baseline, 6 and 12 hours after peritonitis induction, the animals underwent general and coronary hemodynamic evaluation, including determination of autoregulatory breakpoint pressure and adenosine-induced maximal coronary vasodilation for coronary flow reserve and hyperemic microvascular resistance calculation. Endothelial-derived vasodilator response was assessed both in vivo and ex vivo using bradykinin. Coronary arteries were sampled for pathobiological evaluation. Results: Sepsis resulted in a right shift of the autoregulatory breakpoint pressure, decreased coronary blood flow reserve, and increased hyperemic microvascular resistance from the 6th hour after peritonitis induction. In vivo and ex vivo endothelial vasomotor function was preserved. Sepsis increased coronary arteries expressions of nitric oxide synthases, prostaglandin I2 receptor and of prostaglandin F2α receptor. Conclusion: Autoregulation and metabolic blood flow regulation were both impaired in the coronary circulation during experimental hyperdynamic sepsis, although endothelial vasodilatory response was preserved.